MARITIME MANAGEMENT STRATEGY IN REDUCING INDONESIAN SECURITY THREAT ENVIRONMENT PLASTIC MARINE DEBRIS AN: CASE STUDY IN 2018 – 2025 - Amalia Diah Savitri; Ganjar Widhiyoga; GPH Dipokusumo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Marine Plastic Debris is one of the threats of the environment threatened society, in domestic and international. The threat happens because of the factors that caused the human behavior, then it cause the damage to nature and a threat itself for a country. Because there is no waste management plastic that has been used copiously. The problem of Marine Plastic Debris resulted in the number of the impact that caused, ranging from the environment because of the damage marine ecosystems, the economy of the coastal society who decreased, to the public health. As a result of the problem, Marine Plastic Debris makes an important problem that should be handled by the Indonesian government. This is because it can be one of the closure developments in Indonesia. This study tried to analyze how the government’s strategy of Indonesia in management of plastic marine debris for tackling a security threat to the environment. The results of this research are able to give a few clarity about how the obligation, responsibility, and a form of protection that should be given by the country. Keywords: Marine Plastic Debris, Obligation and Responsibility, Security Environment, Strategies of the Government.